Potencial adsorvente da casca e polpa de moringa na remoção de corante orgânico em solução aquosa - Escobar, Otávio dos Santos (2019)
Historically the main environmental degradation factors are linked to industrial processes. The textile and food industries use high volumes of water in their processes. These industries use products such as preservatives, seasonings, detergents, starters and dyes, and end up generating a large volume of contaminated effluents. Improper disposal of these effluents causes damage not only to biota but also to humans. Due to this problem, studies are required to understand e create tecniques to remove contaminants from aqueous media. An alternative is the use of biosorbents, which do not generate toxic byproducts, have low cost, efficiency and availability. From the present work it is verified that the Moringa oleifera has high capacity in the adsorption of dyes in aqueous media. Thus, we sought to characterize the peel and pulp of M. oleifera in natura and evaluate its use in the adsorption of blue dye in aqueous solution. In this work the characterization of the moringa seed husk and pulp was performed. For this the analysis, a Scanning Electron Microscopy, Brumauer-Emmett-Teller method, analysis of chemical compounds, pHPCZ, X-ray Diffraction and Infrared Spectroscopy were performed. . After this characterization, in order to understand the origin of the adsorptive capacity of these materials, the adsorption tests were performed. For this, a preliminary test was performed to optimize the adsorption capacity and soon after were made adsorption kinetics, changes in dye concentrations, and adsorption isotherms, and changes in the temperature. Both models were adjusted to better represent the capacity. As a result we found that the moringa seed husk and pulp have distinct characteristics and adsorption capacity, but both have the potential to remove bright blue dye in aqueous medium.